GAMBARAN KADAR CO DI KABIN PENGEMUDI BUS BRT KOTA SEMARANG - Nugroho, Bayu Yoni Setyo; Haikal, Haikal (Dian Nuswantoro Semarang, 2024)
Public transportation that is often used by the public for daily activities such as working, traveling and traveling in Indonesia is the bus. According to the data obtained the growth of buses every year. Traffic congestion is a condition on any network as vehicle usage increases and is characterized by slower speeds, longer travel times, and increased queues. Carbon monoxide gas has the characteristics of being odorless, imperceptible, and colorless. Motor vehicles contribute greatly to the increase in dangerous CO levels. The purpose of this study was to see CO levels in the cabin of BRT drivers in Semarang City. This research is a basic or descriptive research with the MQ7 Sensor is a carbon monoxide gas sensor that functions to determine the concentration of carbon monoxide (CO) gas in everyday life. The results of CO results were carried out in 3 corridors, namely 4, 7 and 8. The results of CO levels in corridor 4 were highest 15.2 ppm and low 8.8 ppm. The highest CO content results in corridor 7 at 21.1 ppm and the lowest at 13.0 ppm. While the results of CO levels in corridor 8 resulted in 19.2 ppm and the lowest 8.2 ppm.